Biofertilization Enhances Productivity and Nutrient Uptake of Foxtail Millet Plants. Issue 1 (2nd January 2016) - Khatri, Deepti; Durgapal, Anjala; Joshi, Prasoon K.
ABSTRACT: Rhizobacteria are biofertilizers that promote plant growth and development. This study was conducted to evaluate the potential of rhizobacteria for improving productivity and the nutrient level of foxtail millet ( Setaria italica ). Bacillus sp. and Rhizobium sp. were isolated from the rhizosphere and root nodules of a local crop ( Macrotyloma uniflorum ) of Uttarakhand. Seeds of foxtail millet were subjected to four treatments, including control. Under pot culture, all treatments [seeds inoculated with Rhizobium sp. (T-1), seeds inoculated with Bacillus sp. and soil supplemented with 50 g of tri-calcium phosphate (TCP) per pot (T-2), and seeds inoculated with Bacillus sp. (T-3)] significantly improved yield, chlorophyll content, nutrient uptake, and protein in seeds in relation to the control. Total dry weight of plants increased by 122.78% with Rhizobium sp., 59.49% with Bacillus sp. +TCP, and 86.07% with Bacillus sp. treatment; and grain yield increased by 76.29%, 51.39%, and 36.55%, respectively, over the control. We have demonstrated thatT-1 treatment ( Rhizobium sp.) reduced maturation period of the crop by 15 days. Rhizobium sp. was judged to be the best bio-inoculant, indicating possible use of Rhizobium sp. as a potent biofertilizer for foxtail millet. Thus, there is a scope for the development of bio-inoculants for nutrient-poor soils, which may help enhance production and nutritive value of foxtail millet. These results provide baseline information, suggesting the possible role of these bacterial strains as plant growth-promoting rhizobacteria (PGPR) in advancing eco-friendly, sustainable agriculture.